Pengalaman Mahasiswa Dalam Mengatasi Depresi - Ardi, Wandria Robi; Dwidiyanti, Meidiana; Sarjana, Widodo; Indra Wiguna, Reza (Universitas Muhammadiyah Magelang, 2021)
The phenomenon of depression is the many events that occur among students, among the factors that cause students to experience psychological problems due to unpleasant student experiences, such as academic problems, parental demands, bullying, breaking up relationships with spouses. The phenomenon of psychological problems and depression in these students requires further treatment, to prevent more severe impacts. This study uses a qualitative research design, focus of this research is lies in the depth and process, this study involved 4 participants as students. Data collected through participants writing answers to questions (written answer), answers written by participants were read repeatedly carefully, analyzed, made keywords, then categorized from each participant's answers. The results of this study indicate that the experience of students in dealing with depression problems is still diverse in terms of coping mechanisms for psychological problems, both positive and negative coping, among the 4 participants studied there three themes were then analyzed during the data review process including isolating self and activity; pray and worship God, looking for solutions, trust, and discussion in the family. The coping mechanism with a spiritual approach is a way to deal with depression experiences in students.